(untitled) (Perspectivas em Ciência da Informação, 2019)
The strategic use of information is at the core of the intelligence activity whose focus has been largely directed to the use of technology for data analysis. However, the cognitive aspects are the ones that most seem to challenge the transformation of information into intelligence, as they are associated with the psychological dimensions. This paper aims to examine how the big data phenomenon is perceived and influences the activities of strategic intelligence (SI) professionals in Brazil. The research was conducted as a qualitative study. Semi-structured interviews were conducted with 18 leading individuals in the field of strategic intelligence in Brazil followed by a content analysis technique for the data analysis. The results show the effects of big data are less influential over the cognitive dimension of the analyst, particularly in the skills to keep their open-mindedness and in the self-confidence to admit and learn from analytic errors.